Muslim Society's Response to the New Rule of Marriage Age - Bukido, Rosdalina; Harun, Nurlaila; Alwi, Muhammad; Kamaru, Fahri Fijrin (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
This study aims to describe the response of the Muslim community to the new marriage age regulation. The existence of this new provision reaps pros and cons because the community and the government understand the age of marriage, especially Muslim people, who basically consider the age limit for marriage to be when they have reached puberty. This research was conducted in North Sulawesi with a qualitative-descriptive research type and a sociological approach. Data was collected through interviews with informants starting from the community level, religious leaders and community leaders and then analyzed in a descriptive way. The results obtained are that there is a strong religious doctrine and public ignorance of the issuance of Law no. 16 of 2019. With this rule in place, they hinder many couples who are ready to get married. Most people show an attitude of disapproval of the 19-year age limit for marriage. For society, the law does not look good, especially for those who are not yet 19 years old. The community’s understanding is that both partners have reached puberty, as explained in Islamic teachings. Even so, for religious figures to show the opposite attitude, the 19-year marriage penalty rule is very necessary because it involves emotional and economic stability in living a household life. Actually, the implementation of Law No. 16 of 2019 could be more effective if Perma No. 15 of 2019 was also socialized because they related it to the purpose and reasons for the intended marriage age limit. There is a lack of public understanding of the 19-year age limit for marriage because Law No. 16 of 2019, which is socialized, is only a prohibition which prohibits it. Perma No. 15 of 2019 is the answer to the regulatory age limit for marriage at 19 years, which is always questioned in society.